Factors Affecting Indonesian Agriculture Companie’s Disclosure of Biological Assets - Sari Mujiani; Rianto Rianto; Eni Margiati (PT Mattawang Mediatama Solution, 2022)
This study aims to test the effect of Biological Asset Intensity, Managerial Ownership, and Audit on Biological Asset Disclosure on agricultural sector companies listed on the Indonesia Stock Exchange (IDX) Year 2018-2021. Samples were taken using a purposive sampling method with certain criteria, during the study period. Based on the criteria that have been determined by the data using panel data, a total of 68 data were obtained. The analysis method used in this study was the regression analysis of panel data processed using Eviews 9. The results of this study show that (1) Biological Asset Intensity has a significant positive effect on the disclosure of biological assets. This is because the greater the value of biological assets, the higher the company provides more complete and detailed information to users of financial statements. (2) Managerial Ownership has a significant positive effect on the disclosure of biological assets. This is because managers who have a hand in the company's capital will carry out their duties according to applicable regulations and not only for their own interests but also for the sustainability of the company to remain sustainable in the future. (3) The audit has no negative effect on the disclosure of biological assets. This is because the role of kap is not determined by the characteristics of the Big Four or Non-Big Four levels because currently, the role of auditors is growing, many KAP who are not affiliated with the Big Four also revealed that detailed information according to the needs of users of financial statements and investors when choosing the company they will choose as a place to plant shares.